Subsidiarity and Federalism: A Case Study of the Australian Constitution and Its Interpretation - Evans, Michelle (Springer, 2014)
Since the landmark decision of the Australian High Court in the Enginee1:1• case, the Australian federation has become increasingly centralised to the extent that Australia has become less than an authentic federation. This paper evaluates whether the principle of subsidiarity, which is a fundamental characteristic of a federal system of government, could be implemented in Australia to restore legislative and financial powers to the Australian states. The chapter suggests specific constitutional and other reforms.